The Experience Of A Mother Whose Toddler Had Stunted Growth But Has Successfully Recovered : A Phenomenology Study - Atik Pramesti Wilujeng; Novita Surya Putri; Dinda Ayu Permata Hati (PROFESSIONAL HEALTH JOURNAL, 2025)
Stunting is a failure to growth and development in children due to chronic malnutrition. Stunting toddlers cannot escape the supervision of parents, especially mothers who are experienced in caring for stunted toddlers. This Study aimed to exploring the experience of stunted toddler mothers who recovered from stunting. This research used phenomenological qualitative research. Data collection was done by in-depth interview. The participants were 6 mothers who had a stunted toddlers who has Successfully Recovered From Stunting in the working area of the Gitik health center, Banyuwangi. Purposive sampling method was used to select participants according to the inclusion criteria. The study were analyzed using the Colaizzi approach. The study result revealed 5 themes ; grieving, information, personal motivation, social motivation and behavioral skills. The experience of mothers who have stunted toddlers in caring for their children often shows feelings of grief by going through several stages, in order to recover from stunting, the mother's ability to care for her child is also needed, including loving patterns, sharpening patterns, and parenting patterns that children has successfully recovered from stunting Introduction: Mothers who have stunted children will feel ashamed and inferior because they feel they have failed to care for their children. Mothers also feel worried about the future and development of their children These various responses will be a mental burden for mothers (Tresna Darmawan Putri et al., 2024). Based on data on stunted toddlers in Banyuwangi Regency, there has been a decrease in stunting cases, especially in the Gitik Health Center (Dinas Kesehatan Kabupaten Banyuwangi, 2020) Objectives: The Exploration Of Experience Of A Mother Whose Toddler Had Stunted Growth But Has Successfully Recovered Methods: This study uses a qualitative design with a phenomenological approach. Results: The study result revealed 5 themes ; grieving, information, personal motivation, social motivation and behavioral skills. Conclusions: The experience of stunted toddler mothers who recovered from stunting is a sense of grief consisting of stages of grief and the impact of grief. The experience of stunted toddler mothers who recovered from stunting is information consisting of health education. The experience of stunted toddler mothers who recovered from stunting is personal motivation consisting of enthusiasm and obstacles felt. The experience of stunted toddler mothers who recovered from stunting is social motivation consisting of home visits from cadres, integrated health posts, integrated health post parks, riding odong-odong, assistance with nutritional intake and vitamins. The experience of stunted toddler mothers who recovered from stunting is behavioral skills consisting of fulfilling nutrition, providing multivitamins and routine child growth and development checks Keywords must contain at least three to five keywords representing the main content of the article